Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.biochem.5b00137
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Characterization of a Ferredoxin:Thioredoxin Reductase-like Enzyme from Methanosarcina acetivorans

Abstract: Bioinformatics analyses predict the distribution in nature of several classes of diverse disulfide reductases that evolved from an ancestral plant-type ferredoxin:thioredoxin reductase (FTR) catalytic subunit to meet a variety of ecological needs. Methanosarcina acetivorans is a methane-producing species from the domain Archaea predicted to encode an FTR-like enzyme with two domains, one resembling the FTR catalytic subunit and the other containing a rubredoxin-like domain replacing the variable subunit of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 31 publications
(84 reference statements)
2
38
0
Order By: Relevance
“…However, plant ferredoxin:thioredoxin reductase (FTR) is devoid of flavin and contains a novel active-site [Fe 4 S 4 ] cluster (3,4). Methanosarcina acetivorans, classified in the domain Archaea, produces a planttype ferredoxin:disulfide reductase (FDR) also devoid of flavin that contains an active-site [Fe 4 S 4 ] cluster revealed by the crystal structure (5). FDR is representative of a diverse family of disulfide reductases proposed to have evolved from an ancestral plant-type FTR catalytic subunit to meet a variety of specific ecological needs (6,37).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, plant ferredoxin:thioredoxin reductase (FTR) is devoid of flavin and contains a novel active-site [Fe 4 S 4 ] cluster (3,4). Methanosarcina acetivorans, classified in the domain Archaea, produces a planttype ferredoxin:disulfide reductase (FDR) also devoid of flavin that contains an active-site [Fe 4 S 4 ] cluster revealed by the crystal structure (5). FDR is representative of a diverse family of disulfide reductases proposed to have evolved from an ancestral plant-type FTR catalytic subunit to meet a variety of specific ecological needs (6,37).…”
mentioning
confidence: 99%
“…Preliminary characterization of FDR involved ferredoxin (Fdx)-dependent reduction of GSSG, a nonphysiological substrate absent in methane-producing species from the domain Archaea (methanoarchaea) (5). Although FDR homologs are widely distributed among diverse methanoarchaea, the physiological redox substrates are unknown (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been investigated significantly in the anaerobic organisms (6 -24) focusing on both the characteristics of the Trxs and TrxRs (6,8,9,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21)(22)(23) and their physiological roles (6,7,10,14,20). For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7).…”
mentioning
confidence: 99%
“…Work with Clostridium pasteurianum, an anaerobic fermentative bacterium, has revealed a ferredoxin-dependent flavin containing TrxR (8). Similarly, there have been several reports on the Trx and TrxRs of anaerobic archaea (9,15,(17)(18)(19)(20)(21)(22)(23), including the methanogenic archaea, which are strict anaerobes (9,17,18,(21)(22)(23). Recently, a proteomics study has shown that there is clear potential for a Trx-based global redox regulation of metabolism, including methanogenesis, in Methanocaldococcus jannaschii, a strictly anaerobic and deeply rooted hyperthermophilic methanogenic archaeon that lives in deep-sea hydrothermal vents (20).…”
mentioning
confidence: 99%